Degradation by Solar Radiation of Estrogenic Hormones Monitored by UV-Visible Spectroscopy and Capillary Electrophoresis - Fonseca, Ana Paula
This work aims to study the degradation of estrone, 17 beta-estradiol, 17 alpha-ethinylestradiol, and estriol under direct solar radiation, with an average irradiance value of 5.2 kWh/m(2). Degradation at different temperatures (4A degrees C, 20A degrees C, and 30A degrees C) was also tested in darkness. Individual solutions of the four estrogens were prepared and subjected to the conditions referred to above. The degradation for each compound was followed, after 7, 14, 21, 28, 35, 63, 91, and 126 days measuring the absorbance at the wavelength of 281 nm. The degradation of the four mixed estrogens was determined using capillary electrophoresis (CE), with a diode array detector and cholic acid, sodium salt plus sodium borate as a background buffer. The results showed no significant degradation rates on samples subjected to different temperatures. However, the results from CE analysis showed that, under direct solar radiation, after 126 days, the degradation rate varied between 75% and 100%. Also, the UV-Vis showed significant changes in the shape of UV-Vis spectra under direct solar radiation.